Local Community Response to Livelihood Commodification in Tanjung Bira Beach Tourism Destination - Yusuf Hermawan; Darmawan Ardiasnyah (Mahogany Journal De Social, 2024)
This study investigates the local community's response to livelihood commodification in the Tanjung Bira Beach tourism destination. Using a qualitative descriptive approach, data were collected through in-depth interviews and document analysis involving key informants, including community leaders and local business owners. The findings reveal significant impacts of tourism on traditional livelihoods, with many participants experiencing declines in fishing and farming activities while adapting by diversifying into tourism-related work. Cultural practices have also been commodified, raising concerns about authenticity and cultural identity. Despite the economic benefits of increased income and job opportunities, the community faces challenges related to environmental degradation and social tensions. The study highlights the importance of community engagement in decision-making processes and the need for sustainable tourism practices to ensure equitable benefits for all residents.